1989
DOI: 10.1152/ajpheart.1989.257.3.h996
|View full text |Cite
|
Sign up to set email alerts
|

Acidosis depresses delayed afterdepolarization in guinea pig myocardium

Abstract: We examined the relationship among intracellular sodium activity (aiNa), intracellular pH (pHi), and delayed afterdepolarization (DAD) in guinea pig ventricular papillary muscle fibers exposed to K-free solution in vitro, using Na+- and H+-selective microelectrodes. In unstimulated papillary muscles, exposure to K-free solution caused a rapid increase in aiNa of 16.2-22 mM at the end of a 20-min superfusion period with rates of 0.51-0.73 mM/min. This was paralleled by a decrease in intracellular pH of 0.10-0.1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

1993
1993
2016
2016

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…This is important because earlier studies have shown an important and complex relationship between changes in pH, [Na + ] i , and rate of stimulation, 43 which may have implications for the generation of DADs. 44 Finally, unlike in other experimental models such as dogs, 45 mouse Purkinje fibers exhibit a similar density of the inward rectifier K + current ( I K1 ) in PCs and VMs, as shown in our earlier study. 19 Thus, I K1 does not play a role in the preferential formation of DADs in PCs compared with VMs, at least in mice, but this cannot be ruled out for other species, including humans.…”
Section: Discussionsupporting
confidence: 54%
“…This is important because earlier studies have shown an important and complex relationship between changes in pH, [Na + ] i , and rate of stimulation, 43 which may have implications for the generation of DADs. 44 Finally, unlike in other experimental models such as dogs, 45 mouse Purkinje fibers exhibit a similar density of the inward rectifier K + current ( I K1 ) in PCs and VMs, as shown in our earlier study. 19 Thus, I K1 does not play a role in the preferential formation of DADs in PCs compared with VMs, at least in mice, but this cannot be ruled out for other species, including humans.…”
Section: Discussionsupporting
confidence: 54%
“…The double barreled ion-selective microelectrodes were constructed and calibrated as described previously (8,34,35), using liquid-sensor cocktails (hydrogen ionophore Icocktail B, model 95293; Fluka Chemika-Biochemika, Buchs, Switzerland) for H+. Two capillaries were designated as tube A for a reference electrode measuring transmembrane potential and tube B for the ionic sensor.…”
Section: Double Barreled Ion-selective Microelectrodesmentioning
confidence: 99%